2014
DOI: 10.1371/journal.pone.0090509
|View full text |Cite
|
Sign up to set email alerts
|

Radiologically Isolated Syndrome: 5-Year Risk for an Initial Clinical Event

Abstract: ObjectiveTo report the 5-year risk and to identify risk factors for the development of a seminal acute or progressive clinical event in a multi-national cohort of asymptomatic subjects meeting 2009 RIS Criteria.MethodsRetrospectively identified RIS subjects from 22 databases within 5 countries were evaluated. Time to the first clinical event related to demyelination (acute or 12-month progression of neurological deficits) was compared across different groups by univariate and multivariate analyses utilizing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
241
3
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(263 citation statements)
references
References 29 publications
11
241
3
8
Order By: Relevance
“…23 These results suggest that RIS may reflect a more benign entity, but longitudinal data on the natural history of RIS are needed to better understand its prognosis. 4,5,11,18 Whether individuals with RIS should receive MS treatment is debated, 32,33 but a clinical treatment trial is already planned. 34 Due to the low incidence of RIS, conducting studies on patients with RIS may necessitate large nation-based cohorts or multicenter studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 These results suggest that RIS may reflect a more benign entity, but longitudinal data on the natural history of RIS are needed to better understand its prognosis. 4,5,11,18 Whether individuals with RIS should receive MS treatment is debated, 32,33 but a clinical treatment trial is already planned. 34 Due to the low incidence of RIS, conducting studies on patients with RIS may necessitate large nation-based cohorts or multicenter studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore of further interest to determine the frequency of RIS in clinical practice. 3,5,[11][12][13][14][15][16][17][18] However, despite the interest in RIS, its epidemiology remains largely unclear. Postmortem studies have shown a prevalence of incidental MS findings ranging from 0.06% to 0.7%.…”
mentioning
confidence: 99%
“…Involvement of the spinal cord parenchyma is correlated with disability outcomes in MS, [1][2][3] as well as higher conversion rates to clinically definite MS and risk for a first clinical event related to central nervous system demyelination in clinically and radiologically isolated syndromes, respectively. [4][5][6][7] To improve visualization of the spinal cord, cervical and thoracic segments are acquired separately. Unfortunately, previous scientific efforts either focused on the cervical spine exclusively or lacked differentiation between clinical correlations of the cervical versus thoracic spine.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately in two-thirds of the patients develop radiographic progression within the first 5 years. When the number of lesions in the MRI is high (> 9), gadolinium (Gd) enhancement of the asymptomatic lesions is present and in particular if cervical cord lesions are seen, clinical conversion rate is higher (2,5,6,7,17,18,19). In our study, 8 of 49 patients had subsequent neurological episodes during the follow-up period, and thus began to be followed by a diagnosis of Clinically Isolated Syndrome (CIS) -MS accordingly.…”
Section: Resultsmentioning
confidence: 73%